HUBUNGAN POLA KOMUNIKASI PENYULUH PERTANIAN DENGAN PENINGKATAN PENGETAHUAN PETANI SAYURAN DI KELURAHAN TOBUUHA KECAMATAN PUUWATU KOTA KENDARI - Rivan, Rivan; Wunawarsih, Ima Astuty; Buana, Tjandra (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2024)
The process of delivering information carried out by agricultural extension workers to vegetable farmers requires an appropriate communication pattern to increase the level of knowledge of target farmers. The purpose of this study was to determine the relationship between communication patterns of agricultural extension workers and vegetable farmers in Tobuuha Village. The study population consisted of all vegetable farmers in Tobuuha Village, which amounted to 20 farmers and one field agricultural extension worker. The research sample was determined by the census method, resulting in a sample size of 21 individuals. Data were collected through survey techniques, interviews, and the use of documentation, with the assistance of media in the form of questionnaires. This study is a quantitative research study. The data were processed using descriptive analysis through the use of the class interval formula and correlation analysis through the Spearman Rank formula, with the help of SPSS Software Version 26. The research findings indicate that the communication patterns of agricultural extension workers with vegetable farmers in Tobuuha Village encompass one-way, two-way, and multi-directional communication patterns. One-way communication patterns and multi-way communication patterns are classified as medium, while two-way communication patterns are classified as high. The level of knowledge of vegetable farmers is classified as medium based on indicators of understanding, application, and analysis. While the level of knowledge of vegetable farmers based on indicators of knowing is in the low category, the relationship between communication patterns of agricultural extension workers and the level of knowledge of vegetable farmers is statistically significant (0.046) and positive (0.691). This indicates that the more effective the communication patterns employed by agricultural extension workers, the greater the likelihood of increased knowledge among vegetable farmers.